1990
DOI: 10.3109/10715769009109676
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mechanisms of Protection Against Oxidative Stress in Doxorubicin-Resistant Rat Tumoral Cells in Culture

Abstract: We have compared some mechanisms involved in the defense against doxorubicin-induced free radical damage in rat hepatoma and glioblastoma cell lines and their doxorubicin-resistant variants presenting an overexpression of the multidrug resistance gene. Immediate in vivo production of malondialdehyde was minor and was not different in sensitive and resistant cells. Alpha-tocopherol was undetectable in all cell lines. Glutathione levels were not different in sensitive and resistant cells and these levels did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Bcl-2 and members of its family are powerful antioxidant agents and may be augmented in MDR cell lines. Similarly, an increased expression of antioxidant enzymes such as glutathione peroxidase or high levels of scavengers such as a-tocopherol present in the cellular membrane have been described (Benchekroun et al 1990, Mazzanti et al 1995. Lucena 1 cells are more resistant to H 2 O 2 and to ultraviolet-A radiation (UVA) than the parental K562 cell line.…”
Section: Resistance To Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 and members of its family are powerful antioxidant agents and may be augmented in MDR cell lines. Similarly, an increased expression of antioxidant enzymes such as glutathione peroxidase or high levels of scavengers such as a-tocopherol present in the cellular membrane have been described (Benchekroun et al 1990, Mazzanti et al 1995. Lucena 1 cells are more resistant to H 2 O 2 and to ultraviolet-A radiation (UVA) than the parental K562 cell line.…”
Section: Resistance To Oxidative Stressmentioning
confidence: 99%
“…A number of MDR cells lines were shown to be more resistant to lipid peroxidation than their parental lines and different mechanisms have been attributed to explain this increased resistance (Benchekroun et al 1990, Hoban et al 1992, Hill et al 1995, Lenehan et al 1995, Mazzanti et al 1995, Kühl et al 1997. Bcl-2 and members of its family are powerful antioxidant agents and may be augmented in MDR cell lines.…”
Section: Resistance To Oxidative Stressmentioning
confidence: 99%
“…We have recently shown that glutathione peroxidase activities were enhanced in doxorubicin-resistant tumor cells in culture, whereas total glutathione S-transferase activities remained unchanged [24]. In an attempt to show if this enhancement has a role to play in detoxifying the peroxides formed from the redox cycling of doxorubicin, we have developed a technique for the evaluation of these peroxides in cultured cells exposed to the drug [25].…”
mentioning
confidence: 99%
“…Doxorubicin is well known to exert oxidative stress to cells (41). The cytotoxicity of RCC cells to doxorubicin combined with sorafenib was investigated.…”
Section: -------------------------------------------------mentioning
confidence: 99%